Analysis of Soil and Rock Strength Using Vs30 Value and Ground Shear Strain Based on Microtremor Data in the Pindul Cave Area, Gunung Kidul, Yogyakarta - Fauzi Daffa Hanatha; Tri Waspito Indriatmoko; Wihdah Syamsiyah Qurrotu'aeni (Institut Teknologi Sepuluh Nopember, 2023)
The study of rock and soil strength is one of the roles of geophysics. This study uses the microtremor method to determine the shear velocity at a depth of 30 meters (Vs30) and ground shear strain (GSS) which will show the strength of soil and rock under a force. This study was investigated in the Pindul Cave Area. The samples consisted of karst rock types. This study uses the HVSR method which is analyzed to determine the strength of soil and rock in the study area. The results of the study found that the GSS map in general has a range of values of 3,1x10-1 – 3.0x10-2, with the phenomenon of land subsidence and elastic to plastic soil dynamics. Then, the velocity-S 30 has a general value of the range of 250 m/s - 530 m/s is obtained to have a hard soil type, soft rock classification. based on such values, several zones were created to describe the strength of soils and rocks based on classification. the zone is divided into 3; the weak zone is in the southeastern area, the medium zone is in the area extending from the northwest-southeast direction, and the strong zone is in the northwest area.